RANCANG BANGUN SYSTEM KONTROL ALAT-ALAT LISTRIK MENGGUNAKAN BLUETOOTH BERBASIS MIKROKONTROLER - Ira Zulfa; Hendri Syahputra; Ahyar Faisal (STEKOM PRESS, 2021)
The purpose of this thesis is to produce tangible results in providing comfort or convenience in controlling electrical appliances, including turning on or off lights at home and controlling other electrical appliances. The method used in making the Design of Control System for Electrical Equipment Using Bluetooth Based on the Atmega 328 Microcontroller is a prototype. This research method consists of several stages, library research, analytical methods, design and implementation methods. The results achieved are reducing the number of fires due to electrical short circuits and increasing aspects of comfort and convenience for users as well as people with disabilities and the elderly, who find it difficult to stand or to reach lights and the implementation of infrastructure devices, where a series of these tools can work after bluetooth devices are available in the community. android smartphones. connected to the bluetooth module connected to the arduino microcontroller. Basically, using the principle of this tool, the user must be able to operate a smartphone based on the Android operating system. The conclusion is that this equipment has been tested and can be used as a controller of power tools with a lightweight android smartphone via a Bluetooth connection without having to press the switch button.